Exergetic and economic analysis of two-pass RO desalination proposed plant for domestic water and irrigation. (1st March 2017) - Eshoul, Nuri M.; Agnew, Brian; Anderson, Alexander; Atab, Mohanad S.
Abstract: Improving reverse osmosis desalination through reducing power consumption and improving exergy efficiency for acceptable operation conditions is the objective of this study. It covers the influence of recovery ratio on different two-pass reverse osmosis desalination configurations at different sea water temperature and salinity, focusing on power consumption, cost, exergy efficiency and exergy destruction for a proposed 24000m 3 /day two-pass reverse osmosis desalination plant in Libya. The results show that as the recovery ratio increases the exergy destruction decreases and exergy efficiency increases, with a slight decline in the cost of cubic meter with sea water salinity increase. A configuration incorporating pressure exchanger and energy recovery turbine has the highest exergy efficiency and lowest water cost. While the configuration without these has the lowest total capital cost, it has the highest life time cost due to high power consumption. Highlights: The two-pass RO model is validated against operational data. This model highlights that the two-pass RO with PX+ERT has the highest exergy efficiency and the lowest power consumption. The total capital investment of PX+ERT is the lowest value.